Solid State Bioconversion of Oil Palm Empty Fruit Bunches into Compost by Selected Microbes - Hadi Hassan, Hassan Abdel (2001)
The palm oil industry plays a major role in the economic development of several tropical countries. In processing oil palm fruit for oil extraction, palm oil mills produce a considerable amount of solid wastes in the form of fibres, nut shells and empty fruit bunches (EFB). For every 100 tonnes of fresh fruit bunches processed there will be approximately 20 tonnes of nutshells, 7 tonnes of fibres and 26 tonnes of empty bunches discharged from the mill. In order to prevent environmental pollution, disposal of the oil palm wastes needs prudent handling and consideration. The composting process is currently viewed primarily as a waste management method to stabilise organic wastes. Composting is a management system that uses microbial activity to degrade raw organic material. The stabilised end product (compost) is widely used as a soil amendment to improve soil structure and to provide plant nutrients. These beneficial uses of compost can improve healthy plant production, reduce the use of chemical fertilisers and conserve natural resources. The main objective of this study is to develop an alternative technology for the production of compost from oil palm empty fruit bunches (EFB), using a solid state biconversion technique (SSB), by selected microorganisms. SSB is a process whereby an insoluble substrate, with sufficient moisture, but not free water, can be converted to compost by different microorganisms. It is a simple and cost effective way of treating the organic waste, which requires no complex controls. Three efficient cellulolytic cultures Aspergillus niger, Trichoderma reesei and Phanerochaete chrysosporium were used as inoculum in this study. The strains used did not produce any toxic by-products during the bioconversion processes and they were able to utilise lignin and grow on lignocellulosic materials. Shredded and partially dried EFB (280g) were allowed to compost for 8 weeks using ammonium sulfate as a source of nitrogen with the addition of single and mixed culture innoculum of A.niger, T. resie and P.chrysosporium, and compared to the natural process as control. The composting process was carried out in 1 L flasks and the controlling parameters such as moisture content, temperature and aeration were optimised. The investigation showed that due to inoculation, the period of composting was reduced to four weeks compared to normal composting time of 24 - 32 weeks. In addition to this, the quality of the compost was improved and there was greater production of nitrate and ammoniacal nitrogen due to the accelerated decomposition. During four week period, the total carbon degraded to 54% with mixed culture showing a maximum decomposition, followed by P. chrysosporium 53.4%, A. niger 41%, T. reesie 34.6% and control 22.7%. A maximum increase of total nitrogen content of 92.1% was recorded with mixed culture followed by 77.4% with P.chrysosporium, 67.6% with A.niger, 64.7% with T. reesie and 39% with control. The CIN ratio of 47 in EFB compost improved to 11.34 with mixed culture, to between 12.32 - 18.67 with single cultures and to 26. 14 with control. There was a 60% reduction in the CIN ratio over the control. The addition of mixed culture is therefore shown to be more effective than single culture and natural composting (control). The SSB technique was found to be feasible technology with high potential for EFB conversion into compost. The compost prepared by such techniques was rich in nitrogen, phosphorus, potassium and humus content. The observations of this study will provide future guidelines for the production of non-hazardous environmental friendly organic fertilisers.